2011
DOI: 10.3844/ajavsp.2011.93.99
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Polydextrose on Clinical Signs of Canine Osteoarthritis

Abstract: Problem statement:Osteoarthritis is an inflammatory joint disease associated with loss of cartilage matrix. There is suggestive evidence that the intake of polydextrose fiber has anti-inflammatory activity. It was reasoned that polydextrose may have a positive influence on canine osteoarthritis. Approach: A double-blind, placebo-controlled trial with privately owned dogs was carried out to assess the efficacy of STA-LITE® polydextrose in the treatment of osteoarthritis. With the use of a questionnaire, five cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The evidence that consumption of polydextrose elicits anti-inflammatory activity (Fava et al, 2007;Peuranen et al, 2004) and the observed beneficial effect on canine osteoarthritis (Beynen et al, 2011) could be a basis for the application of polydextrose in petfoods. Polydextrose may be added to dog foods with claims on preventing and/or treating the condition of osteoarthritis.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The evidence that consumption of polydextrose elicits anti-inflammatory activity (Fava et al, 2007;Peuranen et al, 2004) and the observed beneficial effect on canine osteoarthritis (Beynen et al, 2011) could be a basis for the application of polydextrose in petfoods. Polydextrose may be added to dog foods with claims on preventing and/or treating the condition of osteoarthritis.…”
Section: Introductionmentioning
confidence: 98%
“…The symptoms of osteoarthritis are chronic pain, lameness and decreased mobility which is explained by loss of cartilage matrix and synovitis (Henrotin et al, 2005). On the basis of literature data (Fava et al, 2007;Peuranen et al, 2004), we have suggested that the ingestion of polydextrose fiber mediates an antiinflammatory effect, leading to improvement of osteoarthritis in dogs (Beynen et al, 2011). Polydextrose has an inhibitory effect on cyclooxygenase-2 (Makivuokko et al, 2005;Fava et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumption of polydextrose promotes the growth of beneficial bifidobacteria and lactobacilli while preventing the growth of harmful ones, such as clostridia [17,18]. It has been suggested to possess anti-inflammatory actions and to improve the signs of osteoarthritis in canines [19], to increase IgA amount in the rat cecum [20], to reduce cyclooxygenase 2 expression in pigs distal colon, and to reduce lesions in rat colitis model [21]. Furthermore, it has been suggested to improve the absorption of magnesium, calcium [22][23][24][25] and iron [26].…”
Section: Introductionmentioning
confidence: 99%